The Stalactite Forms in the Architecture of the Crimea in the Middle Ages - Kirilko, Vladimir P. (Actual Problems of Theory and History of Art, 2019)
Architectural and structural details in the form of stalactites are known on monuments which belong to different faiths and ethnic groups, and they had a diverse purpose. Earliest objects are represented by such outstanding structures as the portal, the mihrab and the minaret of the Uzbek mosque in the Solkhat (1314), the portal of the medresse Inji-bey Hatun, in the same place (1332/33), the portal and the mihrab of the mosque in Sheikh-Koy (1358). Their architectonics and stylistic features demonstrate the building traditions that prevailed in the territory of Asia Minor during the Seljuk Emirates. After 1475 the stalactite details of the Crimean monuments gradually begin to take on the forms, which are typical of the Ottoman architecture. Also in use were the details of the 14th century, which survived and received a new life in secondary use in a number mosques of the 16th–17th centuries. External mihrabs of the Juma-Jami in the Gözlöw, which was built in the 1552 upon the project of the chief architect of the Porta — Hodzha Sinan’, are reminiscent of classical examples of the Seljuk time. The archway of the durbe Hadji Giray (1501) portal’s in Salachik has architectonics, the sources of which originate in the Anatolian wooden architecture. Among the buildings ofthe 18th century the main mihrab of the mosque in the Pionerskoe village stands out. The construction of its arch in many places is simulated by the use of voluminous geometric ornament of carpet type.